Controllable fabrication of nitrogen-doped porous nanocarbons for high-performance supercapacitors via supramolecular modulation strategy - Chen, Huaxia; Lu, Xingyu; Wang, Haihua; Sui, Dianpeng; Meng, Fanbao; Qi, Wei (Journal of energy chemistry, 2020)
In the present work, we developed a micellar system of milk protein-surfactant (SDS)-graphene to prepare the graphene-based aerogels via hydrothermal and freeze-drying method, in which the novel surface-property of aerogels can be tuned with the decreasing of micellar size in the colloid systems resulting the improved specific surface area. The milk protein also severed as green and sustainable sources to introduce nitrogen heteroatoms into the aerogels. Subsequently, the aerogels were further graphitized and activated to fabricate N-doped porous nanocarbon at 600 °C. The initial surface composition and structure of the aerogel, which was proved, has obvious impact on the final structure of the synthesized nanocarbon materials, and thus influence their electrochemical activity. The optimized nanocarbon materials (MGPC-5), with enhanced specific surface area, degree of graphitization, and nitrogen doping, exhibited excellent capacitance performance and stability in both three-electrode system (518.8 F/g at a current density of 0.1 A/g) and symmetrical electrode system (120.8 F/g at current density of 0.1 A/g and with ~95% capacitance retention after 5000 cycles of charging and discharging at 3 A/g) in KOH. The assembled supercapacitor also shows ideal capacitive properties in series and parallel configurations. Tested with a stable 1.6 V windows in Li2SO4 electrolyte, the symmetric supercapacitor cell exhibits a high energy density up to 36.7 W h/kg. The present work provides a feasible fabrication method for high-performance supercapacitor based on graphene and biomass derived carbon, the proposed surface-property regulation and supercapacitor performance improvement strategy may also shed light on other energy related materials or system. Milk micelles serve as multifunctional biomass additives to compose with graphene oxide for fabrication of nitrogen doped porous nanocarbon materials. The supramolecular interactions between the two components provide effective ability in regulation of the surface and porous property and improvement of the supercapacitor performance of nanocarbons. [Display omitted]